A Gross Morphological Study of Human Postmortem Pancreas in Bangladeshi People (Bangladesh Journal of Anatomy, 2011)
Context: Incidence of pancreatic disease increases day by day in Bangladesh. Recent advances in pancreatic surgery and search for new techniques toward investigation of pancreas are demanding a review of the morphology of the pancreas in Bangladeshi people. Objective: To establish a gross morphological standard of pancreas in Bangladeshi people. Study design: A descriptive type of study. Place and period of study: The study was carried out in the department of Anatomy, IPGM&R, Dhaka from November 1991 to May 1992. Materials: 40 (Forty) pancreases from Bangladeshi cadaver of either sex were taken for the study. Method: The collected samples were divided according to different age and sex and comparative studies were done between different age and sex groups. Result: For both the length and weight of the pancreas, there were no significant differences between male and female in the same age group and in between group B and C in the same sex. Significant differences were found in the same sex when compared between group A & B & group C & A. Conclusion: The observation and results of the present study are expected to standardize the morphology of pancreas in Bangladeshi people. Keywords: Pancreas; morphology. DOI: 10.3329/bja.v8i2.7016Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 56-58